A multi-hop V2V broadcast protocol for chain collision avoidance on highways - Shouzhi Xu; Huan Zhou; Chengxia Li; Yu Zhao (2009 IEEE International Conference on Communication Technology and Applications, 2009)
Currently, the V2V (vehicle to vehicle) network relies on periodic broadcast to disseminate emergency warning messages (EWM) to locations beyond the transmission range of individual nodes. But along with it, there comes the problem of broadcast redundancy, which reduces the reliability and efficiency of the warning system. In this paper, by studying different broadcast strategy, a new efficient IEEE 802.11 based broadcast protocol of communication in vehicle group is proposed for preventing chain collisions occurring frequently on highways. The proposed protocol designs to address broadcast redundancy, transmission latency, reliability problems of multi-hop broadcast on highways, and achieves the purpose by choosing broadcast vehicles which are the furthest ones in a queue on the basis of directive broadcast. We use a realistic vehicular mobility model generated by VanetMobiSim to evaluate the performance of the proposed protocol. The result shows it can effectively handle the redundant problem of EWM and achieve higher reliability but lower transmission latency of message dissemination.